Unveiling the hidden allies of industrial chicory—a metagenomic exploration of rhizosphere microbiota and their impact on productivity and plant health - Leclercq, Lalie; Debarre, Sony; Lloret, Emily; Taminiau, Bernard; Daube, Georges; Rambaud, Caroline; Drider, Djamel; Siah, Ali; Desprez, Bruno; Hilbert, Jean-Louis; Lucau-Danila, Anca (Frontiers in Microbiology, 2025)
BackgroundAs industrial chicory is significant for food, fodder, and medicinal purposes, its cultivation is increasingly crucial for producers. To enhance productivity, resistance, and the nutritional and functional values of this plant, we aimed to investigate its interactions with the microbial environment. We performed the first comprehensive taxonomic and functional characterization of the rhizosphere microbiota associated with industrial chicory, investigating how environmental factors influence its composition.MethodsSix different land plots were simultaneously cultivated with the same chicory genotype in northern France. Using soil analyses and metagenomic approaches, we characterized the diversity of bacterial and fungal communities in the soil microbiome associated with chicory plants and discussed their functional traits.ResultsWe observed significant taxonomic variability, influenced by soil composition and cultivation history across each plot. The presence of chicory plants distinctly shaped the microbial community. Specifically, chicory was found to recruit Streptomyces species that produce plant hormones and Penicillium species that facilitate phosphate solubilization and promote plant growth. Moreover, the plant demonstrated an ability to repel pathogens and adapt to local microbial communities by selectively favoring beneficial microorganisms according to local stresses and nutritional needs.DiscussionOur study represents a comprehensive taxonomic and functional analysis of the Cichorium intybus rhizosphere microbiome, underscoring the pivotal role of soil composition and land-use history. The specific microbial recruitment by chicory was also addressed.